Reconsidering social movement impact on democracy: the case of Spain's 15-M movement. - Flesher Fominaya, Cristina; Feenstra, Ramón A. (Social Movement Studies, 2023)
Social movement impact on democracy has primarily been treated in two ways in the literature: the role of social movements in promoting democratization in the form of regime change; and a more recent literature on the ways social movements initiate democratic innovation in governing institutions and norm diffusion in already existing democracy. In this article, we argue that to fully understand social movement impact on democracy, we need to look beyond these two main approaches, as important as they are. Using the emblematic case of Spain's 15-M pro-democracy movement to illustrate our conceptual proposal, we draw on existing literature to argue that social movements can impact democracy in several key arenas currently not sufficiently considered in the literature. We provide examples of democratic impact emerging from the experimentation around the central problematic of 'real democracy' in the 'occupied squares' to highlight several ways social movements' democratic impact might be explored. We develop the concepts of hybridity and democratic laboratory to analyze these impacts and discuss their relation to contemporary theorizing about democracy and movement outcomes. We argue that adopting this broader approach to the democratic impact of social movements leads to a more nuanced understanding of movement outcomes and 'success'.